Effect of different levels of concentrate supplementation on the performance of Black Bengal goat (Bangladesh Journal of Animal Science, 2012)
Fifteen castrated male goats (12.97±1.46 Kg) aged between 12 and 13 months were used to study the effect of different levels of concentrate supplementation on growth performance and nutrient digestibility in Black Bengal goat under stall feeding. The feeding trial was continued for a period of 75 days where goats were supplied at the rate of 158g DM/kgW.75 /day. The animals were assigned into five dietary treatments: A (Only dal grass as sole feed), B (15% DM from concentrate + 85% DM from dal grass), C (20% DM from concentrate +80% DM from dal grass), D (25% DM from concentrate + 75% DM from dal grass), E (30% DM from concentrate + 70% DM from dal grass). Digestibility of all nutrients was gradually higher (P